Penguatan Pembelajaran Membaca Pemahaman Melalui Model Penilaian Otentik Berbasis HOTS - Arisa Putri, Titania; Sukenti, Desi (UIR Press, 2024)
Learning to read comprehension is considered very important. This is due to the fact that learning to read does not only play a role in improving children's language skills, but more than that, namely in improving students' abilities in studying other subjects. However, in fact, reading learning is still carried out for purely practical purposes, namely that students can answer questions based on the content of the reading text. The low effective reading ability of students at school is an illustration of the failure of reading learning carried out at school. This failure was caused by the various topics discussed in reading not being accompanied by reading strategies that could be used to approach the discourse. Therefore, there is a need to implement an authentic HOTS-based assessment model as a strengthening of reading comprehension learning. Authentic assessment guides learning through the creation of various learning activities carried out by students during learning process. HOTS-based authentic assessment provides a real picture of students' ability to read and provides a measure of achievement.